A Metabolomic Analysis of Omega-3 Fatty Acid-Mediated Attenuation of Western Diet-Induced Nonalcoholic Steatohepatitis in LDLR-/- Mice - Depner, Christopher M.; Traber, Maret G.; Bobe, Gerd; Kensicki, Elizabeth; Bohren, Kurt M.; Milne, Ginger; Jump, Donald B. (PLOS ONE, 2013)
BackgroundNonalcoholic steatohepatitis (NASH) is a progressive form of nonalcoholic fatty liver disease and a risk factor for cirrhosis, hepatocellular carcinoma and liver failure. Previously, we reported that dietary docosahexaenoic acid (DHA, 22:6,n-3) was more effective than eicosapentaenoic acid (EPA, 20:5,n-3) at reversing western diet (WD) induced NASH in LDLR-/- mice. MethodsUsing livers from our previous study, we carried out a global non-targeted metabolomic approach to quantify diet-induced changes in hepatic metabolism. ResultsLivers from WD + olive oil (WD + O)-fed mice displayed histological and gene expression features consistent with NASH. The metabolomic analysis of 320 metabolites established that the WD and n-3 polyunsaturated fatty acid (PUFA) supplementation had broad effects on all major metabolic pathways. Livers from WD + O-fed mice were enriched in saturated (SFA) and monounsaturated fatty acids (MUFA), palmitoyl-sphingomyelin, cholesterol, n-6 PUFA, n-6 PUFA-containing phosphoglycerolipids, n-6 PUFA-derived oxidized lipids (12-HETE) and depleted of C20-22 n-3 PUFA-containing phosphoglycerolipids, C20-22 n-3 PUFA-derived oxidized lipids (18-HEPE, 17,18-DiHETE) and S-lactoylglutathione, a methylglyoxal detoxification product. WD + DHA was more effective than WD + EPA at attenuating WD + O-induced changes in NASH gene expression markers, n-6 PUFA and oxidized lipids, citrate and S-lactosyl glutathione. Diet-induced changes in hepatic MUFA and sphingolipid content were associated with changes in expression of enzymes involved in MUFA and sphingolipid synthesis. Changes in hepatic oxidized fatty acids and S-lactoylglutathione, however, correlated with hepatic n-3 and n-6 C20-22 PUFA content. Hepatic C20-22 n-3 PUFA content was inversely associated with hepatic α-tocopherol and ascorbate content and positively associated with urinary F2- and F3-isoprostanes, revealing diet effects on whole body oxidative stress. ConclusionDHA regulation of hepatic SFA, MUFA, PUFA, sphingomyelin, PUFA-derived oxidized lipids and S-lactoylglutathione may explain the protective effects of DHA against WD-induced NASH in LDLR-/- mice.